Certification of mathematics teachers and its perspective - Stankus, Eugenijus; Šinkūnas, Juozas (Lietuvos matematikos rinkinys, 2023)
The situation of certification of mathematics teachers at Lithuania are considered. It also discuss on the evolution and perspective of certification. The example of profficiency test for teachers is given too.